Difference between breast milk jaundice and breast-feeding jaundice: literature review - Shihab, Rabie Abdul Hakim; Samman, Ahmed Mohammad Bin; Aqeel, Fotoun Abubaker; Ghabrah, Ziyad Tawfik; Ghabrah, Omar Tawfik; Ghannam, Abdullah Nizar; Alasmari, Abdulrahman Hassan; Abahussain, Hessa Abdulkareem; Alsulami, Abdulaziz Abdulrhman; Alamri, Samia Mhros; Babader, Rawan Abdulrahman; Aljehani, Doaa Ahmed (International Journal Of Community Medicine And Public Health, 2021)
Evidence shows that the different etiologies of neonatal jaundice, including breastfeeding and breast milk jaundice, have many different aspects. Therefore, the present study aims to conduct a literature review to compare breastfeeding and breast milk jaundice, ehich will furtherly help physicians and healthcare practitioners to have adequate information to properly establish an accurate diagnosis. The precise cause of breast milk jaundice is unclear. The majority of the suggested etiologies include factors found in human breast milk. Other theories point to possible genetic defects in the infected neonates. It has been reported that pregnane-3a,20ß-diol, epidermal growth factor, interleukin (IL)1ß, alpha-fetoprotein, and ß-glucuronidase are several factors that are solid constituents of the breast milk which may attribute to the development of this jaundice. Reports showed that breast milk jaundice usually develops in 20-30% of U.S. neonates, and most of whom are breastfed. Moreover, studies showed that more than one-third of infants on breastfeeding will eventually have high serum bilirubin levels that are ≥5 mg/dl. Evidence showed that the diagnosis should be considered when the levels of serum bilirubin exceed 5 mg/dl. Breast milk jaundice will usually fade away with no interventions, and in some cases, phototherapy inauguration and breast milk discontinuation might be needed. In breastfeeding jaundice, serum bilirubin levels usually peak within the first five or six days of life due to wrong or inadequate breastfeeding practices, and the management should be done by correcting these habits, while phototherapy might be applied when the bilirubin levels exceed 18-20 mg/dl.